Avaliação na licenciatura em matemática sob a ótica dos discentes: implicações para a aprendizagem e para a formação como docente - Niusarte Virginia Pinheiro (2019)
The main objective of this research is to analyze how undergraduate students of the Teacher Training Course in Mathematics of a IFES (Instituição Federal de Ensino Superior) perceive the evaluation practice of their professors in the Mathematical- content subjects, the implications of these practices in learning mathematical content, and in their training as teachers. It is a qualitative, descriptive, and explanatory research. The major degree and the students were chosen by random non-probability sampling. The data was collected through document analysis, observation of didactic activities, individual interviews, focus groups, social networks ( Facebook and WhatsApp), and analyzed through content analysis, following the proposal of Bardin, and based on theoreticians in the area of learning evaluation and teacher training, as well as on the theory of Bourdieu & Passeron, especially the concepts of habitus, field, and symbolic violence. The literature researched reveals a frailty of systematized theoretical-practical studies about evaluation, its modalities, and roles during the process of teacher training. Due to the high level of academic prestige of the specific-content subjects, the power of imposition and inculcation - leading, consequently, to undervaluing pedagogical-content subjects-, the legitimation and selective character of evaluation, and faced by the challenges to learn specific contents, the students showed an extreme concern with their grades and, therefore, make use of several strategies to reach the approval on these subjects, relegating learning to the sidelines. . The students vaguely notice the hidden and legitimating character of evaluation that, by implicit and dispersed criteria, attributes their grades and classify them, leading to an internalization of the responsibility for their failures and successes, thus, naturalizing repetition of year/semester and drop-out. Immersed in a context in which the pedagogical and evaluation practices are predominantly traditional, with conventional exams as the main reliable instrument of evaluation, the undergraduates’ perspective of evaluation swings from a formative one to a more traditional one, showing the internalization and naturalization in their subjectivities of evaluation as having a classificatory and selective role. In the interlocutors’ discourse, the understanding of evaluation as part of the pedagogical practice is still incipient, contraposing with the dominant perspective. Most students investigated notice that their experiences on the specific-content subjects can positively or negatively influence their training as teachers and show a willingness to take their professors as role models/counter-role models. In Bourdieu’s terms, the undergrads are prone, in a lesser or greater degree, to incorporate the habitus of a Mathematics teacher becoming possible reproducers of traditional pedagogical practice and, consequently, of a classificatory and excludent evaluation in elementary education.